Comparison Of Vitamin D, B12 and Folate Levels In Women with and Without Gestational Diabetes Mellitus Reporting to A Tertiary Care Hospital in Lahore - Khan, Najeeb ullah; Sattar, Abdus; Saeed, Mariam; Rana, Muhammad Zeeshan; Anwar, Hina (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare vitamin D, B12 and Folate levels in women with and without gestational diabetes mellitus (GDM) and to find any association of these markers with GDM. Study Design: Comparative Cross-sectional study. Place and Duration of Study: Pathology Department, Combined Military Hospital (CMH), Lahore Pakistan, from Feb 2023 to Aug 2023. Methodology: Vitamin B12, vitamin D and folate levels were assessed in two groups: those with normal glucose tolerance (Group-A, n=108), and women diagnosed with GDM (Group-B, n=54). The comparison of vitamin levels was conducted using the Mann Whitney U test. The association between these vitamins and fasting blood glucose level was explored using multiple linear regression. Results: Females with GDM had lower levels of vitamin B12 (156 pmol/L vs 198 pmol/L), vitamin D (48 nmol/L vs 59 nmol/L) and higher levels of serum folate (40 nmol/L vs 29 nmol/L). The difference in serum values of folate (p=0.003), vitamin B12 (p=0.001) and vitamin D (p=0.002) between the GDM and NGT groups was statistically significant. Vitamin B12 deficiency was observed in 23.4% (n=38) of the study population. About 86% females (n=140) either had deficient or insufficient vitamin D levels. Folate excess was recorded in 25% (n=40) of the participants. Conclusion: Women with Gestational Diabetes Mellitus had comparatively higher serum folate levels and lower levels of vitamins B12 and D as compared to women without GDM, and there is an association of these vitamins with GDM.